Investigation of structural, spectroscopic, dielectric, magnetic, and in vitro biocompatibility properties of Sr/Ni co-doped hydroxyapatites. Issue 18 (15th September 2022) - Ercan, Filiz; Kayed, Tarek S.; Kaygili, Omer; Bulut, Niyazi; Almohazey, Dana; Ates, Tankut; Al-Ahmari, Fatimah Saad; Ay, Ilker; Demirci, Tuna; Kirat, Gokhan; Flemban, Tahani; İnce, Turan; et al.
Abstract: In this study, the changes caused by Ni and Sr additives on the structural, thermal, dielectric, and magnetic properties of hydroxyapatite (HAp) samples were examined and reported for the first time in detail. Some effects of the Sr/Ni site disorder on the crystallographic, dielectric, and magnetic properties in Sr/Ni-HAp have been examined, as well as their cytotoxicity effects. The addition of Ni affected the morphology of nanoparticles with a low agglomeration increase. Our results showed that the dielectric constant (ε′) and dielectric loss (ε′′) have greater values at low frequencies than at higher frequencies for all the samples. It can be concluded that Ni and Sr additions to the HAp structure contribute to the development of thermal, magnetic, and dielectric properties required to mimic natural HAp in the study conducted with the idea of creating a medical application area for bone healing and regeneration. The cytotoxicity test of the produced nanoparticles and the evaluation of the results were also performed using human foreskin fibroblasts (HFF). The viability of cells after treatment for 48 h ranged between 50 and 75%. While 0.37Ni-0.37Sr-HAp and 1.11Ni-0.37Sr-HAp were similar to 0.37Sr-HAp, 0.74Ni-0.37Sr-HAp had the highest cellular viability. At 0.1 mg/mL, 0.74Ni-0.37Sr-HAp had a viability of 79.97% compared to the untreated control cells. Our Sr/Ni-HAp nanoparticles have promising medical applications in bone healing and regeneration.